Motivasi Kinerja Karyawan dan Pelanggan di Toko Boneka Zachryan Toys - Abizachryan Akbar; Amelia Ramadanti; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Zachryan Toys store is a small industry engaged in the sale of grade ori dolls. This business was founded in 2012 in Kampung Baru, Cikampek, Karawang Regency. Based on the results of interviews with the owner, it is known that there was a decrease in sales turnover in 2019 due to Covid that year and starting to run normally again in 2021. The research objectives to be achieved are; knowing the level of importance and performance level of Zachryan Toys Store, knowing its advantages and disadvantages compared to its competitors, knowing the level of customer satisfaction, and knowing good segmentation, targeting and positioning so that it can determine the right proposal. The 7P concept, namely product, price, place, promotion, physical evidence, people, process and the concept of segmentation, targeting and positioning is used to assist in research on the Zachryan Toys Store in Kampung Baru, Cikampek, Karawang Regency in order to achieve increased sales turnover. Segmentation is divided based on geographic, demographic, psychographic, and behavioral. Today's intense competition in the business world is symptomatic of more rapid development in controlling market share on a macro scale. Macro and micro companies such as the Zachryan toys shop, are flocking to each other to get a marketing place so that there will be competition in fighting for market share and consumers. the number of new competitors caused the turnover of the Zachryan Toys Store to decrease. This type of research is field research (field research) using the field as the main reference. The method used in this research is qualitative. The data obtained were sourced from primary data where researchers conducted interviews, observations at the Zachryan toys store. The results of this study show that the more new competitors there are, the lower the turnover at the Zachryan Toys Store. The results of this study show that the increasing number of new competitors makes turnover at the Zachryan Toys Store decrease, so a good competitive strategy is needed in order to win the competition with other competitors and increase turnover. The Zachryan toys shop should also implement new innovations in doll packaging to differentiate dolls from one another so that consumers are more interested in doll products in the Zachryan toys Cikampek shop, and also the Zachryan toys Cikampek shop must be aggressive in promoting through various online media.Â